Penegakan Hukum Terhadap Illegal, Unreported, Unregulated (IUU) Fishing Dengan Konsep Tanggung Jawab Negara Bendera - Andi Putra Sitorus; Suhaidi Suhaidi (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
The  IUU Fishing law has not been effective so far. One of the reasons for the flag of the ship cannot be fully held accountable, let alone the involvement of the flag State in supporting or at least allowing its vessels to conduct IUU Fishing in other areas. The use of the principle of state responsibility can increase the optimization of fair law enforcement. Strict supervision of the flag state and the use of the principle of due dilligent became important to prevent boats and their fishermen from doing IUU Fishing.  Normative legal research is used to see whether the principles used are appropriate by collecting related legal data and looking at their application to existing cases.